Export Management Model and Taxation Aspects for Coconut and derivatives Case Study Agricultural Enterpreneurs in Matani Village - Wauran, Anita Ludia Vivian; Langi, Treesje Amelia Clara; Kaunang, Anneke Marie; Sepang, Steify M.E.W (Future Science, 2025)
The object of this research is business actors in coconut commodities and their derivatives as part of agricultural businesses in Matani Village, Tumpaaan District, South Minasa Regency. Apart from producing coconuts, these business actors also produce coconut derivative products such as copra, coconut oil, shells, coconut flour and cocopeat which are coconut derivative products. Most of the coconut fruit produced and its derivatives are sold directly without further processing, such as copra, shells, coconut fiber (gonofu). However, nowadays, apart from being sold directly, coconut fiber is also often further processed into cocopeat before being sold. Business actors in coconut commodities and their derivatives are also subjective taxpayers, because they have a NPWP (Taxpayer Identification Number) but have not yet carried out their tax obligations. By reporting their tax obligations, this is due to ignorance of the tax obligations attached to their business activities. The partner businesses that are the object of this research are micro businesses in the agricultural sector which are run as home businesses and are included in the category of micro businesses which have tax obligations as individuals. Likewise, the distribution of sales of coconut and its derivatives is only in the local area and around North Sulawesi, without any export or sales activities abroad. This research aims to find out how export management is in accordance with the regulations and what tax obligations are attached. for export activities of coconut and its derivatives. So this research will produce an export management model and tax aspects that will help coconut business actors and their derivatives in carrying out export activities. This research uses descriptive qualitative research methods with research methods in the form of research stages in which there are research methods with research flows that produce export management and tax aspects.